Corrigendum to: Probiotic reduces vaginal HPV abundance, improves immunity and quality of life in HPV-positive women: a randomised, placebo-controlled and double-blind study (DOI: 10.1163/18762891-bja00079) - P. Xu; U. Mageswary; A.A. Nisaa; S.D. Balasubramaniam; S.B. Samsudin; N.I.B.M. Rusdi; A.R.A. Jerip; C.E. Oon; M.H.A. Bakar; D. Rajendran; J.J. Tan; F.F. Roslan; et al. (Beneficial Microbes, 2025)
Symptomatic vaginal and cervicovaginal conditions include bacterial vaginosis (BV), vulvovaginal candidiasis (VVC), and other sexually transmitted infection (STI)-related conditions with overlapping clinical features. Adjunctive probiotic therapies are increasingly explored to complement standard antimicrobial treatment. This randomised, double-blind, controlled trial examined clinical, microbiological, and immune marker patterns associated with the adjunctive use of vaginal-spray spore-forming probiotics (LiveSpo X-Secret; Bacillus subtilis ANA46, Bacillus clausii ANA39, Heyndrickxia coagulans ANA40; 1 × 109 cfu/ml) in women with BV, VVC, and STI-related co-infections. A total of 120 symptomatic women were randomised (1:1; n = 60 per group) to receive either physiological saline spray (Control) or probiotic spray (LiveSpo X-Secret) for 28 days, in addition to standard treatment. Outcomes included clinical signs and symptoms, pathogen positivity and relative load (real-time PCR), vaginal microbiota composition (16S rRNA sequencing), and IL-1β, IL-8, and secretory IgA (ELISA) at days 7 and 28 versus baseline. No adverse events were reported. Symptom improvement was observed from day 7. By day 28, the X-Secret group showed a substantial reduction in the proportion of patients with ≥3 symptoms/signs (from 68.18% to 4.55%; OR = 6.42, P = 0.0147). Multi-pathogen positivity decreased from 50 to 11.36%. Gardnerella vaginalis relative load decreased 275-fold more in the X-Secret group than in the Control group, calculated based on 2ΔCt ( P = 0.0185). Stratified subsample microbiome analysis indicated increased lactobacilli dominance and reduced dysbiosis-associated genera (Prevotella, Gardnerella). IL-1β and IL-8 levels decreased by 62.98% ( P < 0.0001) and 42.95% ( P = 0.0002), respectively, while sIgA increased by 65.67% ( P < 0.0001). In summary, this two-arm randomised study describes clinical, microbiological, and immune marker patterns associated with adjunctive vaginal-spray Bacillus spore probiotic versus saline spray, both in combination with standard treatment. While causal inferences cannot be drawn, these findings highlight the need for further aetiology-specific and longer-term studies. The trial was prospectively registered at ClinicalTrials.gov (NCT06165354).